2005
DOI: 10.1902/jop.2005.76.10.1758
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Techniques to Obtain Root Coverage on Mandibular Incisors

Abstract: All three of the procedures were effective in obtaining root coverage and improved clinical parameters on mandibular incisors. Overall, the DP + CT and TUN-LAT + CT procedures had greater mean root coverage than the CPF + CT technique. Based on this study, when treating defects > or =3 mm deep, one should consider using the DP + CT or TUN-LAT + CT rather than the CPF + CT. Additionally, when treating multiple defects at a time, one should consider using the DP + CT or TUN-LAT + CT rather than the CPF + CT. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 9 publications
4
38
0
1
Order By: Relevance
“… 7 studies reported comparisons with a combination of techniques (Dodge et al 2000, Duval et al 2000, Rosetti et al 2000, Berlucchi et al 2002, Kimble et al 2004, Trabulsi et al 2004, Shin et al 2007). 7 studies reported comparisons with or between surgical techniques not investigated in the present systematic review (Ricci et al 1996, Ito et al 2000, Paolantonio 2002, Burkhardt & Lang 2005, Harris et al 2005, Bittencourt et al 2006, Bittencourt et al 2007). 1 study was on non‐surgical therapy (Aimetti et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“… 7 studies reported comparisons with a combination of techniques (Dodge et al 2000, Duval et al 2000, Rosetti et al 2000, Berlucchi et al 2002, Kimble et al 2004, Trabulsi et al 2004, Shin et al 2007). 7 studies reported comparisons with or between surgical techniques not investigated in the present systematic review (Ricci et al 1996, Ito et al 2000, Paolantonio 2002, Burkhardt & Lang 2005, Harris et al 2005, Bittencourt et al 2006, Bittencourt et al 2007). 1 study was on non‐surgical therapy (Aimetti et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…As reported previously, 1‐7,9 the majority of defects treated in most studies were located in the maxilla (canines and premolars). For other groups of teeth, such as incisors and molars specifically, similar high rates of success might be achieved as well 131,132,199‐201 . Two practice‐based case series studies suggested that procedures involving CAF procedures may perform better in the maxilla than in the mandible 206,207 .…”
Section: Discussionmentioning
confidence: 96%
“…For the 15 Class III defects, 14 reached 100% CRC, and one reached 80% CRC (98.6% MRC and 93.3% CRC; recession depth range of 4 to 8 mm) 132 . When SCTG‐based procedures were used, overall MRC of 88.8% (80.2% SCTG + CAF, 90.5% SCTG + tunnel + laterally positioned pedicle, and 95.9% SCTG + double papilla flap; P = 0.009) and CRC of 62.7% (20 of 41 defects for SCTG + CAF, 24 of 38 for SCTG + tunnel + laterally positioned pedicle, and 30 of 39 for SCTG + double papilla flap) were found 200 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 97%
“…Thirteen papers were excluded because they were not characterized as RCTs. [22][23][24][25][26][27][28][29][30][31][32][33][34] Three RCTs reported the results from samples containing less than 10 patients per group at final examination, 13,35,36 two studies were classified as randomized non-controlled trials, 37,38 two presented a follow-up period <6 months, 39,40 two did not present a patientbased analysis 41,42 and one included recession areas containing teeth with restorations. 43 Of the 23 included studies, 5,12,15,44-63 fifteen had a splitmouth group study design 5,15,[44][45][46][40][41][42][43][44][45][46][47][48][49][50][51][52][53]57,58,[60][61][62]63 and seventeen were conducted at university dental clinics 5,12,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Reason for exclusion Berlucchi et al 2002 41 Patient-based analysis not presented Burkhardt and Lang 2005 35 Less than 10 patients per group at final examination Ç etiner et al 2003 42 Patient-based analysis not presented Cordioli et al 2001 43 Inclusion of recession areas containing teeth with restorations Daniel and Cheru 1990 22 It is not a randomized controlled trial Harris 1997 23 It is not a randomized controlled trial Harris 2000 24 It is not a randomized controlled trial Harris 2002 25 It is not a randomized controlled trial Harris et al 2005 26 It is not a randomized controlled trial Hirsch et al 2005 27 It is not a randomized controlled trial Jahnke et al 1993 36 Less than 10 patients per group at final examination Lafzi et al 2007 39 Follow-up period <6 months Laney et al 1992 40 Follow-up period <6 months Moses et al 2006 37 Randomized non-controlled trial Muller et al 1998 28 It is not a randomized controlled trial Muller et al 1999 29 It is not a randomized controlled trial Nemcovsky et al 2004 38 Randomized non-controlled trial Rahmani et al 2006 30 It is not a randomized controlled trial Ricci et al 1996 31 It is not a randomized controlled trial Ricci et al 1996 32 It is not a randomized controlled trial Sbordone et al 1988 33 It is not a randomized controlled trial Tal et al 2002 13 Less than 10 patients per group at final examination Wennströ m and Zucchelli 1996 34 It is not a randomized controlled trial j o u r n a l o f d e n t i s t r y 3 6 ( 2 0 0 8 ) 6 5 9 -6 7 1 j o u r n a l o f d e n t i s t r y 3 6 ( 2 0 0 8 ) 6 5 9 -6 7 1 heterogeneity was observed in some group comparisons (Table 3). …”
Section: Studymentioning
confidence: 99%